Spain : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This paper assesses the stability of the Spanish financial system as a whole. Spain's banking system has been steadily progressing since the last Financial System Assessment Program. The authorities have made a significant reform effort. Together with the economic recovery, and support by the European Central Bank's accommodative policies, the banking system has strengthened its solvency and advanced in reducing nonperforming loans. It is critical to keep the reform process moving and to build on the advances made during 2012-16. Completing the restructuring of bank balance sheets is a priority. Enhanced monitoring and supervisory attention to interest rate and liquidity risks are also merited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet